If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4z + 2) + (69 + -4z + y + 19) = 90 Reorder the terms: (2 + 4z) + (69 + -4z + y + 19) = 90 Remove parenthesis around (2 + 4z) 2 + 4z + (69 + -4z + y + 19) = 90 Reorder the terms: 2 + 4z + (69 + 19 + y + -4z) = 90 Combine like terms: 69 + 19 = 88 2 + 4z + (88 + y + -4z) = 90 Remove parenthesis around (88 + y + -4z) 2 + 4z + 88 + y + -4z = 90 Reorder the terms: 2 + 88 + y + 4z + -4z = 90 Combine like terms: 2 + 88 = 90 90 + y + 4z + -4z = 90 Combine like terms: 4z + -4z = 0 90 + y + 0 = 90 90 + y = 90 Add '-90' to each side of the equation. 90 + -90 + y = 90 + -90 Combine like terms: 90 + -90 = 0 0 + y = 90 + -90 y = 90 + -90 Combine like terms: 90 + -90 = 0 y = 0 Solving y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 0
| z+13/4=x | | 4x^2+5x=-10 | | 238.64=3.14D | | X^2-30x+135=0 | | 5x+15=6x+10 | | -n/5-16=-21 | | 4x+13=z*z | | -4.7-2.3y= | | X^2+4x+11=-10 | | -5/6x=7/12 | | 0.5x+0.6=0.2x-0.9 | | 3.55y-7.2y= | | 27-2x=7x | | 6b-b=56 | | 4x^4-2x^2+6=0 | | X^2-9x=29 | | (5X-7)/3=X+5 | | 2n-3[2]=53 | | -2(-2h+6)=-26 | | Y=2-6 | | (4y-2)+3y= | | (4z+2)+(y+19)=90 | | 4p^2-p+3=0 | | (3x-4)=0 | | 3(2x-1)-5=2(2x+3)+4 | | 23z-13z=15 | | 5/7x=45 | | 4x^4-2x^2+8=2 | | -(x-7)+5/3=2(x+9) | | 3x-4y=z*z | | 9+2x/9-x2=6-x | | 3a^3-18a^2+24a=0 |